Chlorination management in commercial fresh produce processing lines. (December 2019) - Tudela, Juan A.; López-Gálvez, Francisco; Allende, Ana; Gil, María I.
Abstract: Despite all the information available and the fact that the fresh produce industry has been active for more than 30 years, chlorination management of process wash water (PWW) still needs to be further optimized. It is necessary to adjust the chlorination management to the demanding goals of avoiding microbial cross-contamination and the presence of disinfection by-products (DBPs). In the present study, two commercial processing plants were examined, and the impact of chlorination management was studied by comparing two chlorine sources (chlorine gas and liquid chlorine) under manual and automatic control procedures. The effect of the reduction of water replenishment rates, product type and cut size, as well as product rinse, were also evaluated. Results showed that there was no presence of chlorate in PWW (<0.001 mg/L) and in the product (<0.001 mg/kg) when chlorine gas alone was used, while chlorate accumulation occurred in water (up to 16 mg/L) and product (>2 mg/kg) when liquid chlorine was combined to cope with the chlorine demand. Chlorination management using the automatic control system led to better free chlorine and pH regulation. pH levels using the automatic control were in the range 5.5–6.5, while pH was in the range 6.5–8.5 when using manual control systems. Fluctuations in the physicochemical and microbiological characteristics of PWW were linked to changes in product type and cut size. Chemical oxygen demand (COD) of PWW was twice as high when shredded lettuce was washed (1000–1800 mg/L) compared with chopped lettuce (500–900 mg/L). The microbial load in PWW was higher when washing baby leaves (≈4.0 log cfu/100 mL) compared with cut lettuce (≈2.5 log cfu/100 mL), and higher when washing shredded lettuce compared with chopped lettuce. Product type and cut size significantly affected chlorate residues removal by produce rinse. Tap water rinsing led to significant reductions (p < 0.05) in chlorate concentration in the case of chopped lettuce, but not in the case of shredded lettuce and baby leaves. This study highlights the importance of adequate chlorination management for chlorate residue mitigation, including the selection of chlorine source, control system, and proper water rinse. The concept that 'one size does not fit all' should be present when establishing the operational procedures for different commodities and product formats. Highlights: Chlorine gas does not lead to the presence of chlorate in the industrial wash water. With high chlorine demand, liquid chlorine is added and chlorate accumulates. Automatic chlorination management maintains optimum free chlorine and pH. Product type and cut size affect physicochemical and microbial water characteristics. Product rinse should be optimized to reliably eliminate chlorate on the product.